Long-term results of the enzyme glutation system activity in experimental ovarian cancer - Yershova, L.; Yeromenko, R.; Savytskyi, I.; Alexandryna, T.; Sarakhan, L. (Journal of Education, Health and Sport, 2022)
The article presents the experimental results of the investigation the glutathione system activity (glutathione peroxidase and glutathione reductase) in rats simulated ovarian ascites tumor. In the experimental carcinogenesis of the ovaries, the activity of glutathione reductase and glutathione peroxidase was inhibited at all intervals of the study during long-term observation. After the presence of carcinogenesis in the body, the number of reactions that do not lead to complete utilization of metabolites. Glutathione reductase activity increases between 4 and 6 months. And the activation of glutathione peroxidase for the entire period only decreases. The experiment showed that gammaglobulin with long-term treatment can increase the activity of the glutathione system.